Technology Integration in English Language Learning During the COVID-19 Pandemic: A Review - Sildon, Gwyneth A. (Journal of English Language and Pedagogy (JELPA), 2025)
In response to the closure of academic institutions during the COVID-19 pandemic, the integration of technology was adopted and expanded more than ever. With existing studies being more generalized in scope, this systematic review aimed to establish the effects of technology integration, particularly in English language learning, and identify the recommendations offered in recent studies. An analysis of 44 peer-reviewed, open-access journals led to the identification of the effects and recommendations of technology integration. Following thematic analysis, the review indicates that technology integration produces positive effects, such as improved language skills, enhanced learning experiences, better socialization, and increased efficiency, outweighing its few negative aspects. With these, while technology use is encouraged in learning, caution is necessary to avoid misuse. It is then recommended that instructional methods be designed to maximize these positive effects and address the negative ones. Teacher training also needs to be reinforced and updated with the emerging technology. Generally, this study affirms the value of technology as an effective tool for enhancing language learning when used strategically.